Insumos biológicos no crescimento inicial do trigo - (:unkn) unknown (Universidade Federal do Pampa, 2022)
Biological inputs based on growth-promoting bacteria generate stimuli in plants, through mechanisms such as production of phytohormones, phosphate solubilization, phytopathogen antagonism, among others, being a sustainable technology that can provide the reduction of chemical fertilizers. The objective of this work was to analyze the effect of biological inputs based on Bacillus and Azospirillum brasilense species on the initial growth of wheat. The experimental design was completely randomized, with 4 treatments and 5 repetitions, with each repetition containing 25 plants. The treatments were organized as follows: without inoculation of bacteria (control); seed treatment with Azospirillum brasilense; seed treatment with Bacilus subtiles, B. amyloliquefaciens, B. pumilus (Biotrio); Seed treatment with Biotrio and Azospirillum brasilense. After receiving the proper treatment with biological inputs, 25 seeds were sown in acrylic gerbox boxes containing sieved soil, totaling 125 plants per treatment. The evaluation took place 30 days after sowing, and the following evaluations were carried out: shoot length, root length, number of leaves, length of the largest leaf, shoot fresh mass and root fresh mass, shoot dry mass and from the root. According to the observed results, for the number of leaves there was no significant difference, and the average of the treatments was 3.8 leaves per plant. For the length of the largest leaf, seeds treated with A. brasilense had a lower average (22.12 cm), but when treated with Biotrio + A. brasilense, the increase was 8.6% (24.20 cm), being the best treatment. For shoot length, seeds treated with Biotrio + A. brasilense (30.62 cm) were superior to the other treatments by up to 9.9%, and for root length, the treatment with Biotrio + A. brasilense was also superior (38.67 cm) to the other treatments by up to 45%, but did not differ from the control (29.85 cm) and Biotrio (29.24 cm) treatments. For shoot fresh mass, there were no significant differences between treatments, with a general average of 0.32g per plant, but for shoot dry mass, seeds treated with Biotrio (0.042 g) and with Biotrio + A. brasilense (0.040 g) were superior to the other treatments. For fresh mass (0.27g) and dry mass (0.036 g) of root, the treatment with Biotrio + A. brasilense presented higher averages than the treatment with A. brasilense alone, of 55 % and 44 %, respectively, although it did not differ of the control and Biotrio treatments. Concludes that the treatment of wheat seeds with the biological input based on Bacillus species (Biotrio) associated with the input Azospirillum brasilense brought benefits to the initial growth of wheat.
Biological inputs in the initial growth of wheat
Keywords: Bactérias promotoras de crescimento; Azospirillum brasilense; Bacillus subtilis; B. amyloliquefaciens; B. pumilus; Growth promoting bacteria; CNPQ::CIENCIAS AGRARIAS